Pengaruh Disiplin, Kompensasi Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Perusahaan Umum Daerah Air Minum (PDAM) Tirta Satria Kabupaten Banyumas - Pangaestika, Kinanty (DFAME Digital Financial Accounting Management Economics Journal, 2024)
The Tirta Satria Regional Public Company for Drinking Water (PDAM) Banyumas Regency in 2023 has problems related to employee performance. Through interviews and pre-research data acquisition, there is a phenomenon regarding low discipline, unfair compensation, lack of incentives and organizational culture that is still not properly implemented towards the values or norms of employees. This study aims to find out how the influence of discipline variables, compensation and organizational culture on employee performance. Using descriptive quantitative methods with SPSS version 26.0. The total population is 275 people, the sampling technique uses purposive sampling with the slovin formula so that a sample of 69 people is obtained. The results of this study show that partially; Discipline has a positive and significant impact on employee performance, compensation has a positive and significant impact on employee performance and organizational culture has a positive and significant impact on employee performance. Simultaneously, discipline, compensation and organizational culture affect employee performance. The determination coefficient of 0.351 means that the variables in this study have an effect of 35.1% and the remaining 64.9% are influenced by other factors that were not studied in this study. So to solve the problems that occur, employees and companies must work together in improving discipline, compensation and organizational culture to create optimal employee performance.